AGRICULTURE AND ECONOMIC OUTPUT IN WEST AFRICA: A PANEL DATA INVESTIGATION OF KEY DETERMINANTS - Mabengba David Aja Kofi; Suryanto; Mulyadi (RADJA PUBLIKA, 2026)
This study examines the impact of Agricultural Land Area, Labor Force in Agriculture, Rainfall, and Trade Openness on Agriculture, Forestry, and Fishing, Value Added (% of Gross Domestic Product) across 13 West African countries from 1991 to 2022. Using panel data regression, the analysis shows that Agriculture Land Area and Labor Force Agriculture have a positive influence on Agriculture, Forestry, and Fishing, Value Added (% of Gross Domestic Product), although this effect is limited by land degradation and low labor productivity. RF has a positive but inconsistent impact due to its dependence on rain-fed agriculture, whereas TO significantly boosts growth through market integration. Country-specific factors, like infrastructure and policy frameworks, influence these relationships. These results underscore the importance of policies that optimize land use, enhance labor skills, mitigate climate variability, and expand market access, aligning with Sustainable Development Goals 2 (Zero Hunger) and 8 (Decent Work and Economic Growth).